Analisis Putusan Pengadilan Negeri Kelas I A Kota Bekasi No. 266/PDT.G/2023/PN.BKS Tentang Wanprestasi - Bambang Sunaryo; Wiwi Uswatiyah; Ernawati Ernawati (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This journal examines the decision of the Bekasi District Court in civil case number 266/Pdt.G/2023/PN.Bks involving a contract dispute between PT Annisa Bintang Blitar and PT Berkat Putra Mandiri. The analysis includes the legal basis used by the judge, the considerations in the decision, and the impact of the decision on civil law in Indonesia. Because this case involves a contract dispute between two companies regarding the implementation of contractual obligations and compensation. The method of writing that will be used is the method of statutory approach and literature study of secondary data by means of an inventory of secondary legal materials, secondary legal materials used are in the form of scientific papers, journals, articles, and literature related to the agreement.